Functional domains of a positive regulatory protein, PHO4, for transcriptional control of the phosphatase regulon in Saccharomyces cerevisiae. - Ogawa, N (1990)
The PHO4 gene encodes a positive regulatory factor involved in regulating transcription of various genes in the phosphatase regulon of Saccharomyces cerevisiae. Besides its own coding region, the 1.8-kilobase PHO4 transcript contains a coding region for a mitochondrial protein which does not appear to be translated. Four functional domains were found in the PHO4 protein, which consists of 312 amino acid (aa) residues as deduced from the open reading frame of PHO4. A gel retardation assay with beta-galactosidase::PHO4 fused protein revealed that the 85-aa C terminus is the domain responsible for binding to the promoter DNA of PHO5, a gene under the control of PHO4. This region has similarities with the amphipathic helix-loop-helix motif of c-myc protein. Determination of the nucleotide sequences of four PHO4c mutant alleles and insertion and deletion analyses of PHO4 DNA indicated that a region from aa 163 to 202 is involved in interaction with a negative regulatory factor PHO80. Complementation of a pho4 null allele with the modified PHO4 DNAs suggested that the N-terminal region (1 to 109 aa), which is rich in acidic aa, is the transcriptional activation domain. The deleterious effects of various PHO4 mutations on the constitutive transcription of PHO5 in PHO4c mutant cells suggested that the region from aa 203 to 227 is involved in oligomerization of the PHO4 protein.